Does Basil III Implementation Impact on Financial Performance?.Evidence from Omani's Commercial Banks - Bilal, Zaroug Osman; Salim, Badreldin F. (International Journal of Economics and Financial Issues, 2016)
This research aims to investigate and examine the impact Basel III Implementation on financial performance of commercial banks in Omani. The annual data for all Omani commercial banks during 2013-2015 are used for calculating key financial ratios in order to assess the impact of Basel III implementation on financial performance in Omani commercial banks. To test whether there is a relationship between Basel III implementation and profitability in commercial banking sector , the research used a correlation analyses model, Ordinary and Least Square (OLS) estimation obtained from an SPSS 17.0 package is adopted to analyze the relationship between the variables, where financial performance or profitability of commercial banks was measured in terms of return on assets (ROA),return on equity (ROE) , efficiency ratio (EFR), net Interest margin (NIM) and debt-to equity ratio. The findings of the research established a positive impact of Basel III implementation on financial performance of commercial banks in Oman, however this impact is not statically significant Keywords: Basel III, Commercial banks, Financial performance, Oman JEL Classifications: G 33, G35, M44